Studying the effect of adding growth factors to the autologous melanocyte keratinocyte suspension in segmental vitiligo. Issue 3 (8th April 2020) - Esmat, Samia; Bassiouny, Dalia; Saleh, Marwah A.; AbdelHalim, Dalia; Hegazy, Rehab; ElHawary, Marwa; Gawdat, Heba; Gouda, Heba; Khorshied, Mervat; Samir, Nesrin
Abstract: Addition of different growth factors to the medium used in autologous melanocyte‐keratinocyte transplantation procedure (MKTP) was reported in the literature. The aim of the current study was comparison of response to MKTP in segmental vitiligo (SV) with and without adding growth factors to the suspension medium. Eighteen cases with SV were randomly divided into two groups. In group A: Ham F12 medium was used for suspension and in group B: 5 ng/mL recombinant basic fibroblast growth factor (bFGF) and 25 mg/500 mL 3′5′ cyclic adenosine monophosphate (cAMP) were added to the medium. All cases received NB‐UVB twice weekly for 24 weeks. The area of vitiligo lesions was measured before and after therapy by point‐counting technique and complications were recorded. Excellent response (90%‐100% repigmentation) occurred in 5/9 cases (56%) in group A and 7/9 cases (78%) in group B (with growth factors). A significant decrease in the area of treated lesions before and after therapy was found in both groups A and B ( P = .0012 and .0004, respectively), however, a higher percentage of reduction in area of vitiligo was seen in group B cases (70% in group A vs 90% in group B; P value: .028). Marginal halo was seen in five cases in group A and six in group B. In conclusion addition of bFGF and cAMP to MKTP medium improved the results of the procedure. It could be considered if economically feasible.